Deep Breathing Exercise Mengatasi Pola Napas Tidak Efektif Pasien Penyakit Paru Obstruktif Kronis (PPOK) - Ardelia Salsabilla Azwar; Pauzan Efendi; Husni Husni (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory condition that significantly impacts patients' quality of life. This study explores the Deep Breathing Exercise technique in the context of COPD patients with ineffective breathing patterns. The aim of this analysis is to evaluate the effectiveness of deep breathing exercises in improving breathing quality and reducing breathlessness symptoms in COPD patients. The analysis method involves a case study to examine the positive effects of deep breathing exercises on lung capacity and breathing patterns in COPD patients. The study's results indicate that integrating deep breathing exercises into routine COPD management therapy can provide significant benefits in managing their symptoms. The practical implications of these findings underscore the importance of a holistic approach in designing therapeutic interventions to enhance the quality of life for patients with chronic respiratory conditions like COPD.